2006
DOI: 10.1017/s002531540601424x
|View full text |Cite
|
Sign up to set email alerts
|

The ocean sunfish Mola mola: insights into distribution, abundance and behaviour in the Irish and Celtic Seas

Abstract: Here we provide baseline data on the distribution and abundance of Mola mola within the Irish and Celtic Seas, made during aerial surveys from June to October during 2003^2005. These data were considered in conjunction with concurrent observations of three potential jelly¢sh prey species found throughout the region: Rhizostoma octopus, Chrysaora hysoscella and Cyanea capillata. A total area of 7850 km 2 was surveyed over the three years with an observed abundance of 68 sun¢sh giving a density of 0.98 ind/100 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 21 publications
5
36
0
1
Order By: Relevance
“…Ocean sunfish were also occasionally observed breaching (13.4% of all records) which may decrease parasite load [63]. Our observations support Open Journal of Marine Science previous studies on sunfish being active in coastal, temperate seas during summer [3] [6]. It has also been suggested that the increased presence of smaller, young sunfish in coastal waters may be owing to local current regimes carrying them further inshore than adults [3].…”
Section: Ocean Sunfish (Mola Mola)supporting
confidence: 87%
“…Ocean sunfish were also occasionally observed breaching (13.4% of all records) which may decrease parasite load [63]. Our observations support Open Journal of Marine Science previous studies on sunfish being active in coastal, temperate seas during summer [3] [6]. It has also been suggested that the increased presence of smaller, young sunfish in coastal waters may be owing to local current regimes carrying them further inshore than adults [3].…”
Section: Ocean Sunfish (Mola Mola)supporting
confidence: 87%
“…Recent studies, using pop-up satellite archival tags to establish swimming patterns and thermal preferences (Seitz et al 2002;Bass et al 2005), acoustic transmitters to record patterns of diel movement (Cartamil and Lowe 2004) and aerial surveys of distribution and abundance (Houghton et al 2006), have indicated that ocean sunfishes are active swimmers. A possible migration route of group A, ''northward from Micronesia through Ogasawara Island to the Pacific coast of northeastern Japan,'' as also found with the skipjack Katsuwonus pelamis and the yellowfin tuna Thunnus albacares (Joseph et al 1988), may well explain the distribution pattern of group A around Ogasawara Island and the Pacific coast of northeastern Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Large numbers of the European storm petrel, Hydrobates pelagicus (Linnaeus), forage in the Celtic Sea during the summer months and may take from the sea surface small fish, plankton, mollusks, crustaceans, and V. velella, as do Leach's storm-petrels in the northeast Pacific (Vermeer & Devito, 1988). Other probable predators of V. velella in Irish waters include the ocean sunfish, Mola mola (Linnaeus), and leatherback turtles, Dermochelys coriacea Vandelli, which feed on surface aggregations of gelatinous prey (Houghton et al, 2006b).…”
Section: Velella In Irish Seasmentioning
confidence: 99%